1999
DOI: 10.1046/j.1365-2141.1999.01415.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial multiple myeloma: report of fifteen families

Abstract: Summary.To further define the frequency, clinical and biological features of familial multiple myeloma we performed a retrospective study of related patients who presented with multiple myeloma. Most cases of familial multiple myeloma were observed in siblings (10/15), in whom the mean age at diagnosis was similar to unrelated multiple myeloma. In successive generations the mean age at diagnosis was lower. Monoclonal component was identical (IgG kappa) in seven families. Familial history of monoclonal gammopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 9 publications
0
30
0
2
Order By: Relevance
“…There have been many reports of the familial occurrence of myeloma in the literature, implying a hereditary element or a common environmental factor [11][12][13][14][15][16]. Most of these families have been of Caucasian origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many reports of the familial occurrence of myeloma in the literature, implying a hereditary element or a common environmental factor [11][12][13][14][15][16]. Most of these families have been of Caucasian origin.…”
Section: Introductionmentioning
confidence: 99%
“…Brown et al [8] found that cigarette smoking and alcohol intake could not account for the disparity in the incidence rates. Other work has suggested that environmental factors such as exposure to pesticides and solvents or genetic factors such as translocations involving Chromosomes 13 and 14 may play a role [9,10].There have been many reports of the familial occurrence of myeloma in the literature, implying a hereditary element or a common environmental factor [11][12][13][14][15][16]. Most of these families have been of Caucasian origin.…”
mentioning
confidence: 99%
“…A familial occurrence of hematological malignancies like MM, non-Hodgkin's lymphoma and MDS has been described. 10,11,12 Of note is that in our series of patients, the donor and recipient in all three cases were diagnosed with the same hematological malignancy. This leads to the consideration that in addition to older donors particularly in donors with potential for familial malignancies more extensive screening investigations including serum protein electrophoresis and bone marrow aspiration may be reasonable.…”
Section: Cfu-gmmentioning
confidence: 66%
“…[45][46][47] There are several reports of the familial incidence of myeloma, the germline genetics of which have not been established. 48 There are a smaller number of reported instances of familial AL but no genetic studies have been performed on any of these very rare kindreds 49,50 Interestingly, a number of studies have reported that African-Americans have a higher frequency of multiple myeloma and examination of the Department of Veterans Affairs inpatient data base suggests that they also have a higher frequency of AL. 51 Similarly, an extensive autopsy series indicated that Hispanics of Mexican descent seemed to have a higher prevalence of both AL and AA, but neither observation has been confirmed by a formal epidemiologic study nor have they been subjected to genetic analysis; hence, the possibility remains that the effect may be environmental rather than genetic.…”
Section: Amyloidoses Derived From Molecules Involved In Immune Functionmentioning
confidence: 99%